2012
DOI: 10.1161/strokeaha.111.632117
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Graded Activity Training Can Alleviate Persistent Fatigue After Stroke

Abstract: Background and Purpose-Fatigue is a common, persistent consequence of stroke, and no evidence-based treatments are currently available to alleviate fatigue. A new treatment combining cognitive therapy (CO) with graded activity training (GRAT), called COGRAT, was developed to alleviate fatigue and fatigue-related symptoms. This study compared the effectiveness of the COGRAT intervention with a CO-only intervention after a 3-month qualification period without intervention. Methods-This randomized, controlled, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 34 publications
1
140
0
7
Order By: Relevance
“…56 A Cochrane review of 3 small randomised trials (142 people) which included fatigue as an outcome measure found no effective preventative or treatment strategies . 57 One subsequent trial (n=83) without a control arm showed that treadmill aerobic training and cognitive behavioural therapy (CBT) together was better than CBT alone to treat post-stroke fatigue, 58 A small trial (n=19) demonstrated that group education was a feasible treatment. 59 Screening for fatigue is not currently recommended in guidelines.…”
Section: Printed 27 Sep 2013mentioning
confidence: 99%
“…56 A Cochrane review of 3 small randomised trials (142 people) which included fatigue as an outcome measure found no effective preventative or treatment strategies . 57 One subsequent trial (n=83) without a control arm showed that treadmill aerobic training and cognitive behavioural therapy (CBT) together was better than CBT alone to treat post-stroke fatigue, 58 A small trial (n=19) demonstrated that group education was a feasible treatment. 59 Screening for fatigue is not currently recommended in guidelines.…”
Section: Printed 27 Sep 2013mentioning
confidence: 99%
“…Modafinil, which is approved for the treatment of fatigue in shift workers and patients with MS, failed to improve the Multi-dimensional Fatigue Inventory-20 score in a relatively small randomized controlled trial of patients with stroke, although it did have an effect on some secondary endpoints [123]. Cognitive therapy with graded activity training, however, was associated with a decrease in PSF [124]. (As mentioned previously, exercise and fitness training lead to a reduction in circulating proinflammatory cytokines [125][126][127].)…”
Section: Therapeutic Approaches To the Treatment Of Fatigue: A Focus mentioning
confidence: 99%
“…Furthermore, PSF has been found to have a negative effect on quality of life [2,10], rehabilitation outcomes [11], and even mortality [12][13][14]. However, PSF is often misdiagnosed [11,15,16] and evidence-based clinical guidelines for dealing with PSF are scarce [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although no uniform definition of PSF exists, it is generally defined as "a subjective experience of extreme and persistent tiredness, weakness, or exhaustion after stroke, which can present itself mentally, physically or both and which is unrelated to previous exertion levels" [18,27]. Since this definition is intrinsically subjective and no derivative assessment tools have been specifically constructed for patients with stroke, a large variety of fatigue rating scales have been used in research and clinical practice [20,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation